(untitled) (Research, Society and Development, 2021)
The Integrative and Complementary Practices (PIC) are health resources that enable care according to the principles of integrality, and are inserted into a care model that goes beyond the biomedical vision. The objective of this article was to understand the perception of municipal health secretaries about PICs, as well as to identify which PICs were known by them. This is a qualitative and exploratory research, carried out with 22 health secretaries in municipalities of Bahia. Data collection took place between the months of May and November 2018 in the municipalities and in the meetings of the Regional InterManagerial Commission. The interviews were collected through a semi-structured script, recorded, transcribed, and analyzed through thematic content analysis. The study pointed out that all the secretaries know some PIC and have also used them as a therapeutic resource, obtaining positive results; it also identified that only 7 secretaries know the National Policy of Integrative and Complementary Practices (PNPIC) and the municipalities have no law that regulates such PIC; it was also obtained that only 5 secretaries studied PIC in their academic training. It is important that the secretaries know about the PICs and their benefits as powerful resources for health, but not knowing the PNPIC can hinder the operationalization of the implementation of PICs in the health regions where they are managers. It is necessary to articulate the population, health teams, and health managers in the discussion and development of projects and programs that strengthen the PICs as a powerful health resource for comprehensive health care.